Increased Concentrations of Soluble CD40 Ligand, RANTES and GRO-α in Preeclampsia – Possible Role of Platelet Activation - Mellembakken, Jan Roar; Solum, Nils Olav; Ueland, Thor; Videm, Vibeke; Aukrust, Pål (Thrombosis and Haemostasis, 2001)
Activated platelets may release inflammatory mediators that activate leukocytes and trigger inflammatory reactions in endothelial cells. We examined the concentrations of soluble CD40 ligand (sCD40L) and the chemokines RANTES and GRO-α in platelet-free plasma (PFP), and unstimulated and SFLLRN-stimulated platelet-rich plasma (PRP), as well as in platelet pellets before stimulation using enzyme immunoassays. Nineteen women with normal and twenty-one with preeclamptic pregnancies were studied, and several differences between these two groups of pregnancies were revealed (1). Women with preeclampsia had significantly increased concentrations of sCD40L and GRO-α in PFP (2). Platelets from these patients spontaneously released larger quantities of CD40L and RANTES ex vivo (3). When further activated ex vivo by SFLLRN, platelets from preeclamptic women released lower amounts per platelet of CD40L, RANTES and GRO-α (4). The platelet pellets in preeclamptic women contained decreased amounts of CD40L, RANTES and GRO-α per platelet. Our findings suggest enhanced platelet activation in vivo during preeclampsia resulting in increased release of inflammatory mediators, possibly contributing to inflammation, leukocyte activation and endothelial dysfunction in this disorder.
Keywords: Preeclampsia; platelets; CD40L; RANTES; GRO-α; SFLLRN